Advocacy organizations and nutrition policy in Nigeria: identifying metrics for enhanced efficacy - Resnick, Danielle; Anigo, Kola; Anjorin, Olufolakemi Mercy (Health policy and planning, 2022)
Advocacy organizations have played a significant role in the field of nutrition in recent years. However, why are some advocates viewed as more effective than others? This paper derives metrics for assessing advocacy efficacy by first drawing on key insights from the nutrition and public policy scholarship. A set of metrics is proposed to capture the constitutive elements of three concepts that often emerge as critical from that literature: organizational capacity, strong networks and external outreach. Based on a survey of 66 nutrition stakeholders in Nigeria, including at the federal level and within the states of Kaduna and Kano, the metrics are then applied to a set of advocacy organizations within the country. We show that the metrics can provide insights into why some advocacy organizations are perceived as more effective than others by policymakers. Specifically, we find that geographical reach, the share of budget allocated to advocacy, action plans with clear objectives, large networks that include government and non-governmental policy champions, multiple media and dissemination outputs and numerous training events collectively increase nutrition advocates’ visibility to, and influence on, policymakers. Although the metrics are subject to further testing in other country settings and need to be interpreted based on a country’s underlying policy system, they offer a useful starting point for more systematic, comparative advocacy analysis and learning within the nutrition field and beyond.